MANAGEMENT OF HAJJ SERVICES AT THE OFFICE OF THE MINISTRY OF RELIGIOUS AFFAIRS OF NORTH BENGKULU REGENCY - Jerri Nopriyan Anugerah; Hernowo Noviyanto; Mulyadi Gembar (Yayasan Wayan Marwan Pulungan, 2023)
This type of research is qualitative research with the research approach using Management and psychology. At the same time, the informants in this study are the Head of the Hajj and Umrah Organizing Section, the Staff of the Hajj and Umrah Organizing Section, namely: 1) How is the management of Hajj services at the office of the Ministry of Religion of North Bengkulu Regency. 2) What are the supporting and inhibiting factors in hajj services at the Office of the Ministry of Religion of North Bengkulu Regency? The results of the study show that the management of the services of pilgrims at the Office of the Ministry of Religion of North Bengkulu starts from planning, organizing, implementing, and supervising activities in collaboration with Government Institutions that help the successful implementation of the pilgrimage. The forms of services provided at the North Bengkulu Ministry of Religion Office include Hajj registration services, Hajj cancellation, proposals for elderly pilgrims, merging of mahrams who register separately, guidance on Hajj rituals, division of groups and groups as well as protection services for pilgrims. The inhibiting factors encountered can be overcome by having supporting factors in providing services to prospective pilgrims